PROBLEMATICS AND LEGAL DIMENSIONS IN ARRANGEMENT OF SPACE ACCORDING TO LAW NUMBER 26 OF 2007 - Amiludin Amiludin; Muhammad Asmawi (Universitas Muhammadiyah Tangerang, 2020)
The writing of this article starts from the problems that exist in the development situation in each region, especially in spatial planning, almost certainly has the same problem, such as the absence of consistent and strict licensing in development. Such as floods that occurred in urban areas of Jakarta, Bogor, Depok, Tangerang, Bekasi due to the development of the city. It is increasing the number of population, activities, and land requirements both for settlements and economic activities so that there is a change of function that should be used as a conservation area and green open space has turned into a residential area. This research uses the normative legal research method or discusses this problem more to the study of literature or secondary data. The normative legal analysis includes research on constitutional principles, research on legal systematics, research on the degree of vertical and horizontal synchronization, comparison of law, and history of law. Law enforcement on sustainable spatial planning is a very complex phenomenon with various approaches, both legal, social, political, economic and cultural issues so that for the benefit of the community, the interests of the government as well as the harmony of spatial planning, environmental sustainability needs supporting capacity of the environment and resources nature is included in the case of sustainable development.